Understanding the early molecular changes associated with radiation therapy—A preliminary bulk RNA sequencing study - Andrew Miller; Henning De May; David L. Rou; Jayant P. Agarwal; Sujee Jeyapalina (PLoS ONE, 2025)
Introduction Cancer is the second leading cause of death in the United States, with breast cancer being the most commonly diagnosed new cancer in women. Radiation therapy provides well-documented survival and recurrence benefits; however, it can lead to significant adverse effects, such as radiation-induced fibrosis (RIF), which can cause pain and result in poor aesthetic outcomes. The biological mechanisms underlying RIF are not entirely understood and require further investigation to identify potential intervention avenues. In this study, we investigated the biological response to radiation therapy by analyzing non-irradiated and irradiated tissues from breast cancer patients. Materials and methods We collected tissue from breast cancer patients who underwent unilateral radiation and bilateral breast reconstruction. At the time of final reconstruction (post-radiation), samples were collected from both non-irradiated and irradiated reconstruction sites. These samples were analyzed using bulk RNA sequencing, histology, and immunohistochemistry (IHC). Results In fibrous tissue capsules, CLCA2, COL4A5, and COL6A6 were differentially expressed and may be related to reduced micro-vascularization. CXCL9 and PTCHD4 were upregulated within the skin, possibly conferring an increased immune response, while multiple keratin-related genes (KRT6B, KRT17, KRT25, KRT28, and KRT75) were downregulated. In irradiated muscle tissue, there was increased expression of CXCL10 and downregulation of DCD. These results were confirmed using IHC. Conclusions This study highlights the utility of bulk RNA sequencing studies in conjunction with IHC to identify target genes and biological processes responsible for RIF in tissues at final breast reconstruction. Due to the sample size limitation, further research is warranted to understand the role of keratin and collagen genes in regulating epidermal changes, vascularity, and fibrosis.